KONSEPSI DAN IMPLEMENTASI NILAI MORAL TERHADAP PERGAULAN REMAJA - Dina Fitria Amalia; Nurul Quraini Aulia; Siti Tiara Maulia (CV. ADIBA AISHA AMIRA, 2023)
This research is motivated by the problem of adolescent association which is currently often heard in public news. The development of the era that is increasingly rapid makes the association of teenagers degrade if they do not have a strong filter. In the end, it is very important to maintain values ​​and moral education in the current era of modernization with various realizations, so that later it can have good implications for the development and progress of our nation. In this paper the author provides several solutions to form associations in adolescents including strengthening religious values, forming good character among adolescents, improving communication by families, improving manners, and setting time limits when a child is out of the house. The method used in writing is literature review, collecting and reviewing several references that are in accordance with the theme of the writing raised. The results of the literature review conducted by the author include the urgency of building values ​​and morals, deviant adolescent associations, forms of moral degradation in adolescents, and solutions to adolescent social problems.